Innovation diffusion and technology acceptance model in predicting auditor acceptance of metaverse technology - Handoko, Bambang Leo; Ang, Swat Lin Lindawati; Sarjono, Haryadi; Mustapha, Mazlina (Success Culture Press, 2023)
The current phenomenon in the era of the industrial revolution 4.0 is the development of the digital world. One of the latest technologies are virtual reality and augmented reality which creates a new technology, which is the metaverse. Metaverse is a virtual world that allows its users to interact online. The development of the metaverse has made many companies invest in the metaverse. They buy land and build buildings and other facilities virtually across the metaverse. This digital asset has a material value and must be reported in financial statements. Financial reports must be audited to ensure they are free from misstatements that could mislead users of financial statements. Therefore, auditors are required to be able to conduct audits using this metaverse technology. The purpose of this study is to analyze the factors that make auditors adopt metaverse technology, because we have the problem that currently not so many auditors are ready to conduct metaverse audit. We use factors from the innovation diffusion theory and technology acceptance model. The method we use to solve our research problem is quantitative causal analysis. We tested the hypothesis using statistical analysis with structural equation modelling partial least square approach. This research accommodates primary data collected through e-questionnaire. The respondent is an auditor which work in audit firm/public accountant office. The result of our study finds that perceived trialability, users' compatibility, perceived complexity can provide significant influence on user satisfaction. Perceived observability has no significant influence on user satisfaction. Personal innovativeness has significant influence on perceived usefulness, but personal innovativeness has no significant influence on perceived ease of use. Personal innovativeness and perceived usefulness have significant influence on auditors' intention to accept metaverse technology. The implications of this study provide input to the financial auditor profession, that if you want to increase auditors' acceptance of the metaverse technology, then audit firms must focus on increasing the experience of using it among auditors. Thus, the auditor can try in advance about this metaverse technology and understand its use in work.